2022
DOI: 10.3389/fneur.2022.830064
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Relationship Between Chronic Kidney Disease and Cognitive Disorders

Abstract: Chronic kidney disease (CKD) is a rapidly rising global health burden that affects nearly 40% of older adults. Epidemiologic data suggest that individuals at all stages of chronic kidney disease (CKD) have a higher risk of developing cognitive disorders and dementia, and thus represent a vulnerable population. It is currently unknown to what extent this risk may be attributable to a clustering of traditional risk factors such as hypertension and diabetes mellitus leading to a high prevalence of both symptomati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 133 publications
0
23
0
Order By: Relevance
“…There are several theories linking poor kidney function to dementia, including the kidney-brain-axis theory that outlines the possible neuropathologic outcomes of poor kidney function . Increased dementia risk may be a result of the physiological consequences associated with constant blood flow in both the kidneys and the brain .…”
Section: Discussionmentioning
confidence: 99%
“…There are several theories linking poor kidney function to dementia, including the kidney-brain-axis theory that outlines the possible neuropathologic outcomes of poor kidney function . Increased dementia risk may be a result of the physiological consequences associated with constant blood flow in both the kidneys and the brain .…”
Section: Discussionmentioning
confidence: 99%
“…Podvin and others (2016) found that C2orf40 is a neuroimmune factor in Alzheimer’s disease. The SLC47A1 (solute carrier family 47 member 1) protein is expressed in both the kidney and the brain, and recent research has suggested a linkage between kidney diseases and Alzheimer’s disease (Shi and others , 2018; Kelly and Rothwell, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the prevalence and degree of cognitive decline increase with advanced CKD stages. When CKD progresses from Stage 3 to Stage 5, the prevalence of cognitive impairment among patients increases from 20–50% to 70% [ 18 ]. Studies examining the relationship between CKD and cognitive function have focused largely on hemodialysis patients, and little is known about cognitive dysfunction in pre-dialysis Stage 3–4 CKD.…”
Section: Discussionmentioning
confidence: 99%